Pemanfaatan Limbah Bulu Domba Garut Terhadap Kuat Tekan dan Kuat Tarik Beton - Encep Ahmad Husni Mubarok; Dendi Yogaswara; Mochammad Suva Nugraha (Institut Teknologi Garut, 2025)
Garut fleece waste has fibers with a raw yarn breaking value of 1.76 newtons and a length of 2-5 cm. The increasing number of sheep farms produces a lot of fleece waste, but the handling is minimal, even though fleece is difficult to decompose by bacteria and pollutes the environment. The coarse characteristics of Garut sheep fleece make it underutilized as wool material. This study aims to determine the effect of Garut fleece waste mixture on the compressive strength and tensile strength of concrete at the age of 28 days with a mixture variation of 0%, 1%, and 3%. The results of the normal concrete compressive strength test were 22.33 MPa, while with 1% and 3% mixtures were 9.03 MPa and 5.90 MPa, respectively. The split tensile strength of normal concrete was 1.46 MPa, and with 1% and 3% admixture was 1.23 MPa and 1.19 MPa respectively. The test results show a decrease in the compressive and tensile strength of concrete with the addition of Garut fleece waste.